Perspectives on the unemployment problem : possibilities and prospects for employment generation and policy requirements in the area of human resource development - Lisk, Franklin (OECS St John'sAT, 1987)
Discusses characteristics of the OECS economies with special reference to small size, openness, vulnerability to external shocks and natural disasters. Examines recent growth performance of the OECS countries focussing on the question of employment generation. Reviews the extent and distribution of unemployment and underemployment considering some of its causes and origins. Suggests measures which can be adopted to generate employment. Considers policy requirements for human resource development. Stresses the need for reforming the OECS education and training systems in particular technical and vocational training in order to make them responsive to the skill requirements of the economy. Advocates sound manpower planning.